2007
DOI: 10.2478/s11756-007-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic effects of Lavandula stoechas aqueous extracts

Abstract: Lavandula genus is an important member of Labiatae (Lamiaceae) family. People use commonly Lavandula stoechas as a medicinal plant for various diseases around the world and also in Turkey. The aim of this study was to investigate cytotoxic and genotoxic effects of aqueous extracts (40, 80 and 120 g/L) from L. stoechas flowers on Allium cepa root tip meristem cells. For this purpose, A. cepa onion bulbs were treated with the above-mentioned L. stoechas flower extracts for 72 h. Spring water (pH 7.3) was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 27 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…The cytotoxic effects of plant extracts and essential oils can be evaluated through various cytogenetic assays, including the straightforward and relatively inexpensive root-tip assays (Sobita & Bhagirath 2005;Kuras et al 2006;Akinboro & Bakare 2007;Celik & Aslanturk 2007;Sousa et al 2009;Sousa & Viccini 2011). Application of plant-based genotoxicity assays is justifiable since the results attained using such systems generally correlate well with those obtained from analogous mammal-based tests (Celik & Aslanturk 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic effects of plant extracts and essential oils can be evaluated through various cytogenetic assays, including the straightforward and relatively inexpensive root-tip assays (Sobita & Bhagirath 2005;Kuras et al 2006;Akinboro & Bakare 2007;Celik & Aslanturk 2007;Sousa et al 2009;Sousa & Viccini 2011). Application of plant-based genotoxicity assays is justifiable since the results attained using such systems generally correlate well with those obtained from analogous mammal-based tests (Celik & Aslanturk 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Application of plant-based genotoxicity assays is justifiable since the results attained using such systems generally correlate well with those obtained from analogous mammal-based tests (Celik & Aslanturk 2007). In this context, Lactuca sativa L. (lettuce) is widely used in the detection of mutagens and genotoxic compounds in extracts derived from medicinal plants because it exhibits elevated sensitivity to exogenous agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal extracts have been reported to inhibit mitosis (Çelik & Aslantürk 2006;Çelik & Aslantürk 2007;Akinboro & Bakare, 2007). In the present study, methanolic extracts of D. anomala and the highest concentration of C. album decreased the MI in treated A. cepa roots.…”
Section: Examination Of the Results Of Tests With Camellia Sinensis Inmentioning
confidence: 52%
“…The benefits of vegetables and fruits not withstanding however, recent investigations have revealed that many plants used as food or in traditional medicine have mutagenic, cytotoxic and genotoxic effects in in vitro and in vivo assays (Higashimoto et al, 1993;Schimmer et al, 1994;Kassie et al, 1996;Çelik & Aslantürk, 2007). Medicinal herbs have also been shown to cause adverse effects or have the potential to interact with other medications (Zink & Chaffin, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal extracts have been reported to inhibit mitosis and reduce the mitotic index (MI) (Çelik and Aslantürk, 2007;Akinboro and Bakare, 2007) which is attributed to the inhibition of DNA synthesis, blocking in the G2 phase of the cell cycle or inhibition of protein synthesis (Kim and Bendixen, 1987;Polit et al, 2003). The significance of the cytological and chromosomal aberrations such as chromosomal stickiness, chromosome fragments, lagging chromosomes, binucleated cells and micronuclei (MN) observed in these studies has been discussed by other authors (Patil and Bhat, 1992;Singh, 2003;Krishna and Hayashi, 2000;Çelik and Aslantürk, 2010).…”
Section: Discussionmentioning
confidence: 99%